2020
DOI: 10.5005/jp-journals-10071-23453
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Early Warning Score for Prognostication of Critically Ill Obstetric Patient

Abstract: Introduction Obstetric early warning score (OEWS) has been used conventionally for early identification of deteriorating obstetric patients in the labor room and ward settings. This study was conducted to determine if this simple clinical score could be used for prognosticating a critically ill patient in the ICU setting instead of sequential organ failure assessment score (SOFA) and acute physiology and chronic health evaluation (APACHE II) score. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Additionally, previous research has indicated that the best predictor for outcomes for pregnant women with sepsis is SOFA score [ 15 ], and outcomes for patients with postpartum hemorrhage are strongly predicted by both the SOFA and APACHE II scores [ 16 ]. Findings from this study were in agreement with these results as higher SOFA and APACHE II scores upon admission at our institution’s ICU were significantly associated with either longer ICU length of stay or longer hospital length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research has indicated that the best predictor for outcomes for pregnant women with sepsis is SOFA score [ 15 ], and outcomes for patients with postpartum hemorrhage are strongly predicted by both the SOFA and APACHE II scores [ 16 ]. Findings from this study were in agreement with these results as higher SOFA and APACHE II scores upon admission at our institution’s ICU were significantly associated with either longer ICU length of stay or longer hospital length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing maternal mortality has always been an important topic of health care [5]. Many studies have suggested that early identi cation of critical pregnant women and early treatment of high-risk pregnant women through obstetric early warning system is an effective measure to prevent high-risk patients from progressing to the state of urgent rescue or death [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…As is known, pregnancy is associated with many physiological changes involving cardiovascular, respiratory, renal and hematological system, and most of these changes can be re ected by the parameters of vital signs (HR, BP, RR, temperature, and mental status) [2][3][4]. Obstetric early warning systems are predictive models for early identi cation of women at risk, which rely on a phase of partial decompensation in physiology as a window of opportunity to intervene and prevent deterioration [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…'MEOWS' is now extensively used in obstetric practice, but the systems in use vary significantly (Khergade et al, 2020). The physiological parameters commonly included in MEOWS are pulse rate, respiratory rate, systolic pressure, diastolic pressure, temperature, and urine output ml/hr (Table 1).…”
Section: Table 1 Physiological Parameters For Meowsmentioning
confidence: 99%